Peculiarities of temporal bone microtopography during translabyrinth approach - Trosh, R. M.; Shamaev, M. I.; Gudkov, V. V.; Borisenko, O. N.; Malysheva, T. A. (Ukrainian Neurosurgical Journal)
Peculiarities of temporal bone microtopography were studied on the anatomical preparation during translabyrinth approach to tumors of cerebello-pontine angle. The stages and parametres of translabyrinth approach were outlined. Advantages and disadvantages of this approach were considered.